Electrolytic electrode material and preparation method thereof
A high-density electrolytic electrode material is prepared using a combination of specific powders and a controlled sintering process, addressing low density and high production costs, resulting in improved durability and reduced carbon consumption.
Patent Information
- Application Number
- CN202310791944.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-30
AI Technical Summary
Existing electrolytic electrode materials have low density and high production costs, which hinder their industrial applicability and efficiency.
A method involving the preparation of an electrolytic electrode material composed of calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, and modified bentonite powder, using specific ratios and a multi-step sintering process in a controlled atmosphere to achieve high density and improved mechanical properties.
The resulting electrode material exhibits enhanced durability, temperature resistance, and corrosion resistance, with improved density and reduced carbon consumption, leading to extended service life and simplified production processes.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode material preparation, and in particular to an electrolytic electrode material and a preparation method thereof. Background Art
[0002] Electrode materials refer to materials that play an electron transfer or ion transfer role in electrochemical systems such as batteries and electrolytic cells. They all conduct electricity through the directional movement of free electrons, provide a large reaction area, and withstand electrochemical corrosion caused by electrode reactions. The quality and performance of electrolytic electrode materials directly affect the efficiency of electrochemical reactions.
[0003] The patent application with application number CN200710192545.7 relates to the raw material composition and preparation technology of a metal ceramic inert anode with a metal phase gradiently distributed from the outside to the inside, which is suitable for extracting rare earths by molten salt electrolysis. Its composition includes a metal ceramic formed by at least one composite spinel oxide of Ca-Fe-Ni-O and at least one metal phase. Among them, the anode material is composed of the following raw materials in mass proportion: 1% to 50% single metal or alloy, 1 to 99% spinel oxide, and 0.1% to 10% other metal oxides. During the sintering process of the material, the material is selectively oxidized by adjusting the oxygen content in the atmosphere to form a functional gradient structure with a corrosion-resistant outer layer (high oxide content) and a high-strength, high-toughness, and high-conductivity inner layer (high metal content). However, its density is about 82 to 90%, which cannot meet the use requirements. Therefore, the present invention provides an electrolytic electrode material and a preparation method thereof to solve the above problems. Summary of the invention
[0004] The first object of the present invention is to provide a method for preparing an electrolytic electrode material in view of the deficiencies in the prior art, which has a simple process, low production cost and is suitable for industrial production;
[0005] The second object of the present invention is to provide an electrolytic electrode material with high density.
[0006] The present invention adopts the following technical solutions:
[0007] (1) A method for preparing an electrolytic electrode material, comprising the following steps:
[0008] S1, mixing and ball-milling calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and an additive to form an electrode mixture, wherein the additive is a mixture of carboxymethyl cellulose and polyvinyl acetate;
[0009] S2, spray granulating and drying the electrode mixture to form granules, and then placing the granules in a metal mold for compression molding to obtain a green body;
[0010] S3, placing the green body into a nitrogen atmosphere furnace at 400-600°C, keeping it warm for a period of time, and then continuing to raise the temperature to 700-1000°C for sintering; then gradually exhausting the nitrogen in the furnace, inputting air and argon, and continuing to raise the temperature to 1100-1200°C, and keeping it warm for a period of time; then exhausting the air and argon in the furnace, inputting nitrogen and argon, and continuing to raise the temperature to 1300-1400°C, keeping it warm for a period of time, and finally cooling it to room temperature to obtain an electrolytic electrode material.
[0011] Further, in S1, the weight ratio of calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and additives is 1:0.1-0.3:0.4-0.6:0.05-0.08:0.1-0.3:0.5-0.8;
[0012] Furthermore, in S1, the weight ratio of the carboxymethyl cellulose to polyvinyl acetate is 1:1.8-2.1.
[0013] Furthermore, the preparation method of the modified bentonite powder is: stir and mix Al(ClO3)3 and bentonite, add water and stir, let stand, drain and take out the solid phase; roast the solid phase, then cool to room temperature, take out and grind to obtain modified bentonite powder.
[0014] Furthermore, the weight ratio of Al(ClO3)3 to bentonite is 2-3:100, and the particle size of bentonite is 80-120 mesh; the weight ratio of Al(ClO3)3, bentonite mixture to water is 4:6-9, the stirring time after adding water is 1-2 hours, and the standing time is 20-24 hours; the roasting temperature is 800-1000°C, and the roasting time is 1-2 hours.
[0015] Furthermore, the preparation method of the calcined titanium tungsten silicon carbide powder is: titanium powder (purity greater than 99.99%, particle size 50-60μm), tungsten powder (purity greater than 99.99%, particle size 50-60μm), silicon powder (purity greater than 99.99%, particle size 20-30μm), and carbon powder (purity greater than 99.99%, average particle size 20-30μm) are placed in an argon-protected ball mill for ball milling. After the ball milling is completed, the powder is calcined. After the calcination is completed, it is placed in a ball mill for ball milling to obtain calcined titanium tungsten silicon carbide powder.
[0016] Furthermore, the atomic ratio of the titanium powder, tungsten powder, silicon powder and carbon powder is 3.0-3.3:0.01-0.04:1:2.0-2.3; the first ball milling time is 20-24h, the ball mill rotation speed is 370r / min, the ball-to-material ratio is 12:1-3, and the ball diameter is Φ15-20mm; the ball mill and the grinding balls are made of 440C steel; the roasting temperature is 950-1050°C, and the roasting time is 1-1.5 hours.
[0017] Furthermore, in S1, the particle sizes of the calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder and modified bentonite powder are all 40-60 microns; in S2, the diameter of the particles is 5-8 mm; and the particles are formed into green bodies at 200-300 MPa.
[0018] Furthermore, in S3, the green body is kept in a nitrogen atmosphere furnace at 400-600°C for 6-8h; after the temperature is raised to 700-1000°C, the sintering time is 6-8h; after the temperature is raised to 1100-1200°C, the holding time is 0.5-6h; after the temperature is raised to 1300-1400°C, the holding time is 2-4h; the volume ratio of air and argon introduced is 1:1; the volume ratio of nitrogen and argon introduced is 1:1.
[0019] (ii) The present invention also provides an electrolytic electrode material prepared by the preparation method described above, wherein the electrode material is composed of calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and additives; wherein the weight ratio of the calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and additives is 1:0.1-0.3:0.4-0.6:0.05-0.08:0.1-0.3:0.5-0.8; the additive is composed of carboxymethyl cellulose and polyvinyl acetate, and the weight ratio of the two is 1:1.8-2.1.
[0020] Beneficial effects:
[0021] (1) The electrode material of the present invention is composed of calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and additives. The calcined titanium tungsten silicon carbide powder not only has excellent physical properties, but also has excellent mechanical properties, which greatly improves the durability and service life of the electrode. In particular, the role of tungsten in the calcined titanium tungsten silicon carbide greatly improves the temperature resistance. At the same time, adding molybdenum carbide to the electrode not only improves the temperature resistance of the electrode, but also improves the high-temperature corrosion resistance;
[0022] (2) The silicon oxide powder, magnesium oxide powder and modified bentonite powder of the present invention ensure high temperature forming and compaction. The ratio of silicon oxide to magnesium oxide can adjust the high temperature bonding forming of bentonite and also ensure the density of the electrode. The modified bentonite is added with aluminum element to improve the temperature resistance of the high temperature bonding material. The auxiliary component ensures the strength and formability during low temperature forming;
[0023] (3) The electrolytic electrode of the present invention is characterized in that: the electrode does not use graphite carbon, thus saving carbon consumption and reducing the smoke produced by the carbon electrode. It is stronger than the graphite electrode, has better durability and longer life. The replacement or replacement cycle is extended, the production control process becomes simpler, and the labor intensity is reduced. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] The experimental methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.
[0026] Example 1
[0027] This embodiment provides a method for preparing an electrolytic electrode material.
[0028] (1) Preparation of modified bentonite powder:
[0029] Al(ClO3)3 and bentonite (100 mesh) were mixed in a weight ratio of 2:100, water was added in a solid-liquid weight ratio of 4:7, stirred for 2 hours, allowed to stand for 20 hours, drained and the solid phase was taken out; the solid phase was calcined at 800°C for 1.5 hours, then cooled to room temperature, taken out and ground to obtain a 60-micron modified bentonite powder.
[0030] (2) Preparation of calcined titanium tungsten silicon carbide powder:
[0031] Titanium powder, tungsten powder, silicon powder and carbon powder were mixed with an atomic ratio of 3.0:0.04:1:2.0, and placed in an argon-protected ball mill for 20 hours (the ball mill speed was 370r / min, the ball-to-material ratio was 6:1, and the ball diameter was Φ15mm; the ball mill and the grinding balls were made of 440C steel). After the ball milling was completed, the powder was calcined at 950°C for 1.5 hours. After the calcination was completed, it was placed in a ball mill for ball milling to obtain 60-micron calcined titanium tungsten silicon carbide powder.
[0032] (3) mixing and ball-milling calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and an additive in a weight ratio of 1:0.1:0.6:0.05:0.2:0.5 to form an electrode mixture, wherein the additive is a mixture of carboxymethyl cellulose and polyvinyl acetate in a weight ratio of 1:1.8;
[0033] (4) spray granulating and drying the electrode mixture to form pellets with a diameter of 5 mm, and then placing the pellets in a metal mold and pressing at 300 MPa to obtain a green body;
[0034] (5) The green body is placed in a nitrogen atmosphere furnace at 400°C, kept warm for 6 hours, and then the temperature is further increased to 800°C for sintering for 6 hours; then the nitrogen in the furnace is gradually discharged, and air and argon with a volume ratio of 1:1 are input, and the temperature is further increased to 1200°C and kept warm for 2 hours; then the air and argon in the furnace are discharged, and nitrogen and argon with a volume ratio of 1:1 are input, and the temperature is further increased to 1300°C, kept warm for 2 hours, and finally cooled to room temperature to obtain an electrolytic electrode material.
[0035] Example 2
[0036] This embodiment provides a method for preparing an electrolytic electrode material.
[0037] (1) Preparation of modified bentonite powder:
[0038] Al(ClO3)3 and bentonite (100 mesh) were mixed in a weight ratio of 3:100, water was added in a solid-liquid weight ratio of 4:9, stirred for 1 hour, allowed to stand for 24 hours, drained and the solid phase was taken out; the solid phase was calcined at 900°C for 1 hour, then cooled to room temperature, taken out and ground to obtain a 60-micron modified bentonite powder.
[0039] (2) Preparation of calcined titanium tungsten silicon carbide powder:
[0040] Titanium powder, tungsten powder, silicon powder and carbon powder were mixed with an atomic ratio of 3.3:0.02:1:2.3, and placed in an argon-protected ball mill for 22 hours (the ball mill speed was 370 r / min, the ball-to-material ratio was 12:1, and the ball diameter was Φ15 mm; the ball mill and the grinding balls were made of 440C steel). After the ball milling was completed, the powder was calcined at 1050°C for 1 hour. After the calcination was completed, it was placed in a ball mill for ball milling to obtain 60-micron calcined titanium tungsten silicon carbide powder.
[0041] (3) mixing and ball-milling calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and an additive in a weight ratio of 1:0.2:0.4:0.06:0.3:0.8 to form an electrode mixture, wherein the additive is a mixture of carboxymethyl cellulose and polyvinyl acetate in a weight ratio of 1:2.1;
[0042] (4) spray granulating and drying the electrode mixture to form pellets with a diameter of 5 mm, and then placing the pellets in a metal mold and pressing at 200 MPa to obtain a green body;
[0043] (5) The green body is placed in a nitrogen atmosphere furnace at 600°C, kept at this temperature for 6 hours, and then the temperature is further increased to 700°C for sintering for 6 hours; then the nitrogen in the furnace is gradually discharged, and air and argon with a volume ratio of 1:1 are input, and the temperature is further increased to 1100°C and kept at this temperature for 4 hours; then the air and argon in the furnace are discharged, and nitrogen and argon with a volume ratio of 1:1 are input, and the temperature is further increased to 1300°C and kept at this temperature for 3 hours, and finally cooled to room temperature to obtain an electrolytic electrode material.
[0044] Example 3
[0045] This embodiment provides a method for preparing an electrolytic electrode material.
[0046] (1) Preparation of modified bentonite powder:
[0047] Al(ClO3)3 and bentonite (100 mesh) were mixed in a weight ratio of 3:100, water was added in a solid-liquid weight ratio of 4:6, stirred for 1 hour, allowed to stand for 20 hours, drained and the solid phase was taken out; the solid phase was calcined at 1000°C for 1 hour, then cooled to room temperature, taken out and ground to obtain a 60-micron modified bentonite powder.
[0048] (2) Preparation of calcined titanium tungsten silicon carbide powder:
[0049] Titanium powder, tungsten powder, silicon powder and carbon powder were mixed with an atomic ratio of 3.2:0.02:1:2.2, and placed in an argon-protected ball mill for 20 hours (the ball mill speed was 370 r / min, the ball-to-material ratio was 12:2, and the ball diameter was Φ15 mm; the ball mill and the grinding balls were made of 440C steel). After the ball milling was completed, the powder was calcined at 1050°C for 1 hour. After the calcination was completed, it was placed in a ball mill for ball milling to obtain 60-micron calcined titanium tungsten silicon carbide powder.
[0050] (3) mixing and ball-milling calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and an additive in a weight ratio of 1:0.2:0.5:0.06:0.2:0.6 to form an electrode mixture, wherein the additive is a mixture of carboxymethyl cellulose and polyvinyl acetate in a weight ratio of 1:2;
[0051] (4) spray granulating and drying the electrode mixture to form pellets with a diameter of 5 mm, and then placing the pellets in a metal mold and pressing at 200 MPa to obtain a green body;
[0052] (5) The green body is placed in a nitrogen atmosphere furnace at 500°C, kept warm for 7 hours, and then the temperature is continuously raised to 900°C for sintering for 6 hours; then the nitrogen in the furnace is gradually discharged, and air and argon with a volume ratio of 1:1 are input, and the temperature is continuously raised to 1200°C and kept warm for 2 hours; then the air and argon in the furnace are discharged, and nitrogen and argon with a volume ratio of 1:1 are input, and the temperature is continuously raised to 1400°C and kept warm for 3 hours, and finally cooled to room temperature to obtain an electrolytic electrode material.
[0053] Example 4
[0054] This embodiment provides a method for preparing an electrolytic electrode material.
[0055] (1) Preparation of modified bentonite powder:
[0056] Al(ClO3)3 and bentonite (100 mesh) were mixed in a weight ratio of 2:100, water was added in a solid-liquid weight ratio of 4:8, stirred for 1 hour, allowed to stand for 20 hours, drained and the solid phase was taken out; the solid phase was calcined at 800°C for 2 hours, then cooled to room temperature, taken out and ground to obtain a 60-micron modified bentonite powder.
[0057] (2) Preparation of calcined titanium tungsten silicon carbide powder:
[0058] Titanium powder, tungsten powder, silicon powder and carbon powder are mixed with an atomic ratio of 3.1:0.02:1:2.2, and placed in an argon-protected ball mill for ball milling for 20-24 hours (the ball mill speed is 370r / min, the ball-to-material ratio is 12:3, and the ball diameter is Φ15mm; the material of the ball mill and the grinding balls are both 440C steel). After the ball milling is completed, the powder is calcined at 1050°C for 1 hour. After the calcination is completed, it is placed in a ball mill for ball milling to obtain 60-micron calcined titanium tungsten silicon carbide powder.
[0059] (3) mixing and ball-milling calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and an additive in a weight ratio of 1:0.2:0.5:0.08:0.3:0.7 to form an electrode mixture, wherein the additive is a mixture of carboxymethyl cellulose and polyvinyl acetate in a weight ratio of 1:1.9;
[0060] (4) spray granulating and drying the electrode mixture to form pellets with a diameter of 5 mm, and then placing the pellets in a metal mold and pressing at 300 MPa to obtain a green body;
[0061] (5) The green body is placed in a nitrogen atmosphere furnace at 600°C, kept warm for 6 hours, and then the temperature is further increased to 800°C for sintering for 7 hours; then the nitrogen in the furnace is gradually discharged, and air and argon with a volume ratio of 1:1 are input, and the temperature is further increased to 1200°C and kept warm for 3 hours; then the air and argon in the furnace are discharged, and nitrogen and argon with a volume ratio of 1:1 are input, and the temperature is further increased to 1400°C, kept warm for 2 hours, and finally cooled to room temperature to obtain an electrolytic electrode material.
[0062] Example 5
[0063] This embodiment provides a method for preparing an electrolytic electrode material.
[0064] (1) Preparation of modified bentonite powder:
[0065] Al(ClO3)3 and bentonite (100 mesh) were mixed in a weight ratio of 3:100, water was added in a solid-liquid weight ratio of 4:8, stirred for 1 hour, allowed to stand for 20 hours, drained and the solid phase was taken out; the solid phase was calcined at 1000°C for 1 hour, then cooled to room temperature, taken out and ground to obtain a 60-micron modified bentonite powder.
[0066] (2) Preparation of calcined titanium tungsten silicon carbide powder:
[0067] Titanium powder, tungsten powder, silicon powder and carbon powder were mixed with an atomic ratio of 3.0:0.03:1:2.3, and placed in an argon-protected ball mill for 20 hours (the ball mill speed was 370 r / min, the ball-to-material ratio was 12:3, and the ball diameter was Φ15 mm; the material of the ball mill and the grinding balls were both 440C steel). After the ball milling was completed, the powder was calcined at 950°C for 1.5 hours. After the calcination was completed, it was placed in a ball mill for ball milling to obtain 60-micron calcined titanium tungsten silicon carbide powder.
[0068] (3) mixing and ball-milling calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and an additive in a weight ratio of 1:0.3:0.6:0.06:0.1:0.6 to form an electrode mixture, wherein the additive is a mixture of carboxymethyl cellulose and polyvinyl acetate in a weight ratio of 1:1.8;
[0069] (4) spray granulating and drying the electrode mixture to form pellets with a diameter of 5 mm, and then placing the pellets in a metal mold and pressing at 200 MPa to obtain a green body;
[0070] (5) The green body is placed in a nitrogen atmosphere furnace at 500°C, kept warm for 6 hours, and then the temperature is further raised to 800°C for sintering for 4 hours; then the nitrogen in the furnace is gradually discharged, and air and argon with a volume ratio of 1:1 are input, and the temperature is further raised to 1100°C and kept warm for 4 hours; then the air and argon in the furnace are discharged, and nitrogen and argon with a volume ratio of 1:1 are input, and the temperature is further raised to 1300°C and kept warm for 4 hours, and finally cooled to room temperature to obtain an electrolytic electrode material.
[0071] The electrode materials prepared in Examples 1 to 5 were subjected to density tests, and the results showed that the density of the electrode materials prepared in Examples 1 to 5 of the present invention could reach 90-93%, which is higher than the existing technical level.
[0072] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.
Claims
1. A method for preparing an electrolytic electrode material, characterized in that: The following steps are involved: S1, mixing and ball-milling calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and an additive to form an electrode mixture, wherein the additive is a mixture of carboxymethyl cellulose and polyvinyl acetate; S2, spray granulating and drying the electrode mixture to form granules, and then placing the granules in a metal mold for compression molding to obtain a green body; S3, placing the green body into a nitrogen atmosphere furnace at 400-600°C, keeping the temperature for a period of time, and then continuing to raise the temperature to 700-1000°C for sintering; then gradually exhausting the nitrogen in the furnace, inputting air and argon, and continuing to raise the temperature to 1100-1200°C, and keeping the temperature for a period of time; then exhausting the air and argon in the furnace, inputting nitrogen and argon, and continuing to raise the temperature to 1300-1400°C, keeping the temperature for a period of time, and finally cooling to room temperature to obtain an electrolytic electrode material; The preparation method of the modified bentonite powder is as follows: Al(ClO3)3 and bentonite are stirred and mixed, water is added and stirred, the mixture is allowed to stand, water is drained and a solid phase is taken out; the solid phase is roasted, then cooled to room temperature, taken out and ground to obtain the modified bentonite powder; The weight ratio of calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and additives is 1:0.1-0.3:0.4-0.6:0.05-0.08:0.1-0.3:0.5-0.8; The preparation method of the calcined titanium tungsten silicon carbide powder is as follows: titanium powder, tungsten powder, silicon powder and carbon powder are placed in a ball mill protected by argon gas for the first ball milling, and after the ball milling is completed, the powder is calcined, and after the calcination is completed, the powder is placed in a ball mill for ball milling again to obtain the calcined titanium tungsten silicon carbide powder; The atomic ratio of the titanium powder, tungsten powder, silicon powder and carbon powder is 3.0-3.3:0.01-0.04:1:2.0-2.
3.
2. The method for preparing an electrolytic electrode material according to claim 1, characterized in that: In S1, the weight ratio of the carboxymethyl cellulose to polyvinyl acetate is 1:1.8-2.
1.
3. The method for preparing an electrolytic electrode material according to claim 1, characterized in that: The weight ratio of Al(ClO3)3 to bentonite is 2-3:100, and the particle size of bentonite is 80-120 mesh; The weight ratio of Al(ClO3)3, bentonite mixture and water is 4:6-9, the stirring time after adding water is 1-2 hours, and the standing time is 20-24 hours; The calcination temperature is 800-1000°C and the calcination time is 1-2 hours.
4. The method for preparing an electrolytic electrode material according to claim 1, characterized in that: The first ball milling time is 20-24h, the ball milling jar speed is 370 r / min, the ball-to-material ratio is 12:1-3, and the ball diameter is Φ15-20mm; the ball milling jar and the grinding balls are made of 440C steel; The calcination temperature is 950-1050°C, and the calcination time is 1-1.5 hours.
5. The method for preparing an electrolytic electrode material according to claim 1, characterized in that: In S1, the particle sizes of the calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder and modified bentonite powder are all 40-60 microns; In S2, the diameter of the pellets is 5-8 mm; the pellets are formed into green compacts at 200-300 MPa.
6. The method for preparing an electrolytic electrode material according to claim 1, characterized in that: In S3, the green body is kept in a nitrogen atmosphere furnace at 400-600°C for 6-8 h; after the temperature is raised to 700-1000°C, the sintering time is 6-8 h; after the temperature is raised to 1100-1200°C, the holding time is 0.5-6 h; after the temperature is raised to 1300-1400°C, the holding time is 2-4 h; The volume ratio of air to argon gas introduced was 1:1; The volume ratio of nitrogen to argon in the nitrogen and argon gases introduced was 1:
1.
7. An electrolytic electrode material, prepared by the method according to any one of claims 1 to 6, characterized in that: The electrode material is composed of calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and additives; wherein the weight ratio of calcined titanium tungsten silicon carbide powder, silicon dioxide powder, molybdenum carbide powder, magnesium oxide powder, modified bentonite powder and additives is 1:0.1-0.3:0.4-0.6:0.05-0.08:0.1-0.3:0.5-0.8; the additive is composed of carboxymethyl cellulose and polyvinyl acetate, and the weight ratio of the two is 1:1.8-2.1.
